International migration and economic inequality in rural communities: an assessment - Salas-Alfaro, Renato (2012)
This study uses a community in Oaxaca as a case study to analyse the economic inequality experienced in rural communities across Mexico. Given the widespread pattern of international migration in this country, the study highlights the impact of international remittances on inequality. Using the Gini coefficient decomposition technique, the study examines the behaviour and distribution of income and wealth in one-third of the households in a community in the state of Oaxaca. The findings show that this community exhibits high economic inequality and that remittances contribute to this through increased household income and as a means of asset accumulation. Furthermore, they refute the notion that inequality does not exist in indigenous communities, as posited by some indigenists (Bonfil, 1994; Bartra, 1993), and support the hypothesis that recent migration induces economic inequality in rural communities (Stark, Taylor and Yitzhaki, 1986).